USING PICTURE WORD INDUCTIVE MODEL (PWIM) IN TEACHING WRITING RECOUNT-TEXT - Kurniawati, Dewi; Khomariyah, Siti (Universitas Islam Negeri Raden Intan Lampung, 2018)
The aim of this research is to know the influence of using Picture Word Inductive Model (PWIM) towards students’ writing ability in recount text. Picture Word Inductive Model (PWIM) is a strategy to teach writing by using picture that contains objects and events that are familiar to lure students take the words and their vocabulary.The research methodology was experimental research. The population of this research was the students of the tenth grade of SMAN 1 Waway Karya. The researcher took the sample by using cluster random sampling technique. In collecting the data, the researcher applied the test in the form of written test. The test was used for pre-test and post test. After giving the post-test, the researcher analyzed the data by using SPSS independent sample t-test. The result of this research showed that there was influence of using Picture Word Inductive Model (PWIM) towards students’ writing ability of recount text at the second semester of the tent grade of SMAN 1 Waway Karya in the academic year of 2017//2018.Keywords: Picture Word Inductive Model (PWIM), writing, recount text